A QUALITATIVE STUDY OF HOUSEWIVES' CONSUMER BEHAVIOR TOWARDS THE INCREASE IN COOKING OIL PRICES IN SERANG IN 2024 - Edi Sumatirta; Irsyad Thalib Abdillah; Febri Ana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to explore the impact of rising cooking oil prices on consumer behavior, particularly among housewives in Serang City in 2024. The significant price increase during this period triggered various changes in consumption patterns and household financial management strategies. Using a descriptive qualitative approach using survey and interview methods, this study found that the majority of respondents experienced consumption adjustments, such as reducing the frequency of cooking oil use, switching to cheaper brands, and increasing efficiency in monthly shopping. This study shows that consumer behavior is highly responsive to fluctuations in the prices of basic necessities and emphasizes the importance of household economic literacy as a form of preparedness for price crises. The results of this study can be used as a reference in making food policies and strengthening the role of housewives as family economic managers.